Two novel compound heterozygous mutations in NGLY1as a cause of congenital disorder of deglycosylation: a case presentation - Haixia Ge; Qingbin Wu; Huigang Lu; Yong Huang; Tingting Zhou; Danlin Tan; ZhongqinJin (BMC, 2020)
Abstract Background NGLY1-related congenital disorder of deglycosylation (NGLY1-CDDG) is a multisystemic neurodevelopmental disorder in which affected individuals show developmental delay, epilepsy, intellectual disability, abnormal liver function, and poor growth. This study presents a 10-month-old female infant with elevated liver transaminases, developmental delay, epilepsy (subclinical seizures), and constipation who possesses two compound heterozygous mutations in NGLY1. Case presentation The proband was admitted to the Department of Gastroenterology, Children's Hospital of Soochow University, with elevated liver transaminases. She had a history of intrauterine growth retardation and exhibited elevated transaminases, global developmental delay, seizures and light constipation during early infancy. Whole-exome sequencing (WES) and Sanger sequencing revealed two compound heterozygous mutations in NGLY1 that had been inherited in an autosomal recessive manner from her parents. One was a termination mutation, c.1168C > T (p.R390*), and the other was a missense mutation, c.1156G > T (p.D386Y). NGLY1-CDDG is a rare disorder, with a few dozen cases. The two mutations of this proband has not been previously identified. Conclusions This study investigated a Chinese proband with NGLY1-CDDG born from healthy parents who was studied using WES and Sanger sequencing to identify the causative mutations. We identified two novel compound heterozygous mutations in NGLY1, c.1168C > T (p.R390*)/c.1156G > T (p.D386Y), which are probably causative of disease.